Intellectual capital disclosure factors: company age, company size, and gender diversity in property & real estate companies listed on the IDX - Leny Suzan; Salsabilla Putri Anisha (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Intellectual capital disclosure (ICD) is becoming increasingly important to increase corporate transparency and stakeholder trust. This study uses the ICD-In (Intellectual Capital Disclosure-Indonesia) index to examine how different variables affect intellectual capital disclosure. These characteristics include company age, company size, and gender diversity. Secondary data was employed for quantitative research method in this study.  The analysis included all real estate and property companies listed on the Indonesia Stock Exchange from 2018 to 2022. The 85 data observations were purposefully sampled from 17 companies.  The data was analysed using descriptive statistics and panel data regression. Company size, company age, and gender diversity are shown to have an impact on intellectual capital disclosure. Age of company and gender diversity do not effect on the disclosure of intellectual capital; nevertheless, the size of company size has a significant positive effect on intellectual capital disclosure.